The impact of brand ambassadors and brand personality on brand image through brand trust mediation: evidence from Indonesian Cosmetics industry - Tardi, Yesi Erma Cahyani; Septrizola, Whyosi (Universitas Negeri Padang, 2025)
This study aims to analyze the influence of brand ambassadors and brand personality on brand image, with brand trust as a mediating variable, for Wardah Cosmetic products in Tanah Datar Regency. This research is motivated by the decline in Wardah's brand index, which is suspected to be related to the effectiveness of brand ambassadors and the consistency of brand personality. Data was collected through a survey of 250 respondents using a 1-5 Likert scale and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with Smart-PLS software. The results showed that: (1) brand ambassadors have a significant influence on Wardah's brand image in Tanah Datar Regency, (2) brand ambassadors have a significant influence on Wardah's brand trust in Tanah Datar Regency, (3) brand personality has a significant influence on Wardah's brand image in Tanah Datar Regency, (4) brand personality has a significant influence on Wardah's brand trust in Tanah Datar Regency, and (5) brand trust has a significant influence on Wardah's brand image in Tanah Datar Regenc.